Pattern of Self-medication among Undergraduate Medical Students: A Cross-sectional Study (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Self-medication is one of the major emerging health problems. It may lead to many health hazards as well as resistance to antimicrobial agents. Lack of enough report on self-medication in medical students has encouraged to conduct this study. The study aims to find out the pattern, perception and reasons for self-medication in undergraduate medical students. MATERIALS AND METHODS: This descriptive crosssectional study was conducted among undergraduate medical students at Janaki Medical College and Teaching Hospital (JMCTH) from February 2022 to April 2022. A pre-validated questionnaire was used for data collection and was analyzed using SPSS. RESULTS: Total of 134 students participated in this study, with mean age of21.70±1.66 years. 90.3% of students practiced self-medication in last 6 months. Mild nature of disease was the most common reason for self-medication. Fever (65.67%) was the most common cause of self-medication, whereas NSAIDS (45.9%) was most commonly used drugs for self-medication. Pharmacist (52.9%) were the most common source of drug information. Nausea/vomiting (32.09%) was the most common adverse effect experienced by participants. 80.6% thought that selfmedication was a part of self-care. More than one-third had opinion that self-medication was recommended by WHO. CONCLUSIONS: Majority of students practiced self-medication. More than half of them prescribed medication to others. Medical students should be made aware of the harmful effects of self-medication.